Kwan Yin: Een boek van de Goden en de Hel - Borel, Henri, 1869-1933 (Salt Lake City, UT : Project Gutenberg, 2021)
"Kwan Yin: Een boek van de Goden en de Hel" by Henri Borel is a philosophical and artistic exploration of Chinese Buddhism and culture, likely written in the early 20th century. The text delves into the figure of Kwan Yin, the Goddess of Mercy, illuminating her significance in both religious and artistic contexts. Borel emphasizes the emotional and aesthetic experiences that arise from interacting with Kwan Yin's imagery, seeking to evoke the essence of love, compassion, and forgiveness that she represents within the complex tapestry of Chinese spirituality. The opening of the work sets a reflective tone as Borel discusses his previous writings and addresses critiques of his approach, distinguishing his literary style from purely scholarly works. He expresses a desire to convey the beauty and emotion inspired by Kwan Yin, rather than adhering strictly to scientific analysis. Borel introduces Kwan Yin through a rich description of her iconography, likening her to Western figures like the Holy Virgin, and detailing the pivotal role she plays in alleviating human suffering through her compassionate nature. The text invites readers to contemplate the interplay between art, culture, and spirituality, particularly in relation to the divine feminine as embodied by Kwan Yin in Chinese belief systems. (This is an automatically generated summary.)
Release date is 2021-06-06
Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg (This book was produced from scanned images of public domain material from the Google Books project.)
Keywords: China -- Religion; China -- Social life and customs; Guangzhou (China) -- Description and travel; Art -- China